Embedding flexible fibers into responsive gels to create composites with controllable dexterity. Issue 45 (19th October 2016) - Singh, Awaneesh; Kuksenok, Olga; Balazs, Anna C.
Abstract : We designed a stimuli-responsive material integrating a thermo-responsive gel with photo-responsive fibers that exhibits controllable dexterity. Abstract : Using computational modeling, we design a composite that encompasses a thermo-responsive gel and photo-responsive fibers that extend from the surface of the gel. By simulating the effect of light and heat on the sample, we isolate scenarios where cooperative interactions within the system allow the gel to actuate the "finger-like" motion of the embedded fibers. To achieve this distinctive behavior, we consider a gel formed from poly( N -isopropylacrylamide) (PNIPAAm), which shrinks when heated above the lower critical solution temperature (LCST). The fibers are functionalized with spirobenzopyran (SP) chromophores that extend a finite region into the polymer network. The application of heat causes the entire gel to shrink, while the application of light causes the regions around the functionalized fibers to collapse. With the fibers arranged in a square or circular pattern in the center of the gel, heating the non-illuminated samples drives the fibers to move apart as they bend outward (away from the center). With the application of light, the tips of fibers come together as the fibers bend inward. In this configuration, the fibers could act as grippers that bind objects in the presence of light. With the illumination turned off, the grippers could controllably release the objects. By placing the fibers closer to the edge of the sample, the combination of heat and light could be harnessed to bind and release larger objects. We also show that by illuminating the fibers separately, we can manipulate the motion of the individual finger-like objects, and thus, potentially expand the utility of the system. Overall, our findings provide guidelines for controllably reconfiguring the shape of soft materials and thus, tailoring the material to display different functionalities in different environments.